THE INFLUENCE OF LENGTH OF BUSINESS, UNDERSTANDING ACCOUNTING AND BUSINESS SIZE ON THE QUALITY OF FINANCIAL REPORTS (Case Study in Malioboro Area of Yogyakarta) - Vinsensius Engelbertus Lado; Ratri Paramitalaksmi (SEAN Institute, 2023)
Micro, Small, and Medium-Sized Enterprises (MSME) prepare excellent financial reports that become accurate accounting information for tax reporting, bank credit applications, and economic decisions in business management, such as those regarding pricing and market development. This experiment aims to determine factors that affect the duration of business, comprehension of accounting concepts, and size of the firm in order to assist Micro, Small, and Medium-Sized Enterprises (MSME) in preparing financial reports. All of the MSME actors in the Kota Yogyakarta district served as the research's population. The